THE EFFECT OF ALKALI IONIC RADIUS, TEMPERATURE, AND PRESSURE ON THE SOLUBILITY OF WATER IN MALSI3O8 MELTS (M=LI, NA, K, RB) - Behrens H.; Meyer M.; Benne D.; Nowak M.; Holtz F. (My University, 2001)
The solubility of water in melts of alkali feldspar endmember compositions (MAlSi3O8, M=Li, Na, K, Rb) was investigated at temperatures 825–1420°C and pressures 50–800 MPa. Water contents of isobarically quenched glasses were determined by Karl–Fischer titration (KFT) and/or by near-infrared (NIR) spectroscopy.At given P and T conditions, the mole fraction of dissolved water decreases with increasing alkali radius from Li to K. The water solubility differences between Li-, Na- and K-feldspar compositions are more pronounced at low than at high temperature. For instance, at 500 MPa, the solubility ratio is 1:0.84:0.71 at 900°C and 1:0.87:0.82 at 1200°C. The trend of a decreasing water solubility with increasing alkali radius, however, does not hold for Rb. At 1200°C and 400 and 500 MPa, we found a minimum water solubility for K compared to the other alkali (Li, Na, Rb).This result contrasts with the effect of excess alkali oxide on increasing the water solubility in haplogranitic melts which is according to Dingwell et al. [Dingwell, D.B., Holtz, F., Behrens, H., 1997. The solubility of water in peralkaline and peraluminous granitic melts. Am. Mineral. 82, 434–437] on a molar equivalent basis the same for Cs, Rb, K, and Na whereas it is smaller for Li.With increasing pressure, the water solubility turns over from a retrograde to a prograde T-dependence at constant pressure. Normalizing the solubility by the fugacity of H2O a negative dependence on temperature is observed in the whole PT range of our experiments indicating regardless of whether OH groups or molecular H2O are the dominating water species in the melt the dissolution enthalpy of water in the melt is positive.The pressure, Pneutral, at which water solubility is independent on T decreases from 700±100 MPa for LiAlSi3O8 (water content≈16.5 wt.%) to 500±50 MPa for Na (water content 11.5 wt.%) to 200±50 MPa for K (water content 5.2 wt.%). For Rb, quench bubbles indicate Pneutral≪300 MPa. Pneutral might be related to the critical behavior of the silicate–water system. From the observed trend, we infer that the critical curves of the MAlSi3O8–H2O system in the investigated pressure range progressively shift towards higher T with decreasing ionic radius of the alkali.